Preparation and Properties of Water-based Nano-TiO2 Composite Phase Change Material - Ji Jun; Zeng Tao; Zhang Xuelai; Ren Yinglei; Chen Yufeng; Gao Yahan (Zhileng xuebao)
Water is a frequently used cool storage material in the field of refrigeration and food preservation. Because of the large supercooling degree during the phase change period and the low thermal conductivity of water, a composite water-based phase change material containing nanoparticles and a dispersing agent was developed. The mass ratio of the material is H2O+0.7% nano-TiO2+1.0% sodium dodecyl benzene sulfonate (SDBS). The phase change temperature of the composite phase change material is 0.216℃ and the latent heat is 353.1 kJ/kg. By adding nano-TiO2, the supercooling degree of water can be reduced by 5–6℃, while the thermal conductivity increases by 62.7%, from 0.5988 to 0.9745 W/(m?K). Moreover, adding the dispersing agent SDBS improves the sedimentation problems of water-based nano-TiO2, enhances the stability of the material, and prevents the phase separation phenomenon. Through theoretical and experimental analyses of the thermal properties of the composite phase change material with different nano-TiO2 and SDBS ratios, the optimal mass ratio is determined to be 7:10. The color and thermal conductivity of the optimal material after the installation indicate that nano-TiO2 has good dispersion stability in water.